Experimental in utero infection of fetal pigs with a porcine parvovirus. - Bachmann, P A (1975)
In utero infection of fetuses of six specific-pathogen-free large white sows at 35, 48, 55, 72, 99, and 105 days was studied. The fetuses were infected by direct inoculation of porcine parvovirus into the amniotic sac. The inoculation consisted of 0.25 ml of tissue culture fluid containing 10(5.5) mean tissue culture infective doses per ml of porcine parvovirus strain G10/1. Fetuses of one uterus horn were infected, whereas fetuses in the opposite horn were given 0.25 ml of noninfected cell culture material. No clinical signs of infection were observed; however, all sows developed antibodies 7 to 9 days postinfection. A total of 24 virus-inoculated fetuses and 20 control fetuses were studied. Fetuses infected at 35, 48, and 55 days of gestation died between about 5 and 22 days after infection. Virus was isolated from their organs and fetal blood. Virus spread to control fetuses but did not cause death and mummification or stimulate antibody production. Fetuses from sows infected at 72, 99, and 105 days of gestation survived. They developed high antibody titer in utero. Control piglets remained antibody free.